Legal aspects of banking regulation: Common law perspectives from Zambia - Kenneth K Mwenda (Pretoria University Law Press (PULP), 2010)
Legal aspects of banking regulation: Common law perspectives from Zambia by Kenneth K Mwenda 2010 ISBN: 978-0-9814420-7-5 Pages: 330 Print version: Available Electronic version: Free PDF available